Food System Transformations: Brazil, Rwanda, and Vietnam - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Brazil, Rwanda, and Vietnam implemented forward-looking policies that led to their improved food security and nutrition. Alongside strong agricultural productivity growth, high profitability, and improved nutrition, these countries attracted private sector investment along the entire food value chain. The presence of strong partnerships contributed to this success. Governmentled initiatives were complemented with collaborations that led to improvements, including, for example, climate-smart approaches to agricultural production. Further, food system transformations in these countries contributed to significant reductions in hunger and undernutrition. These transformations did not happen without setbacks, however; a common challenge was the issue of inclusive land rights, especially for small farmers. This document describes food system transformations in Brazil, Rwanda, and Vietnam by comparing several aspects of the food system—including interventions in land tenure, nutrition, and finance— against the backdrop of each country’s political economy. It also discusses remaining and emerging challenges in each country. These case studies present a variety of context-specific approaches that could provide lessons for other countries and help pave the way to a transformed global food system.